A CONVERSATIONAL ANALYSIS ENCOUNTERED BY ENGLISH YOUNG LEARNERS: A PEDAGOGICAL EXPERIENCE - Reza Pustika (University of Kuningan, 2021)
This article is written to evaluate the conversational analysis encountered by English young learners. The subjects of this study were 4th-grade students in primary school. Since English serves as a lingua franca, there are a big number of parents who invite their children to learn English. Young learners are frequently involved in speaking discourses. Speaking discourses are quite related to a conversation. This article evaluated the conversational analysis, especially turn-taking encountered by young learners. The use of pictures and a video facilitate the implementation of the activities. The analysis was done by the teacher’s observation during the activities. From the activities, it can be concluded that young learners encounter turn-taking when they are involved in a conversation.Keywords: Young learners; conversational analysis; turn-taking.